Peripheral blocks in pediatric cardiac surgeries: Systematic review (Research, Society and Development, 2024)
Peripheral blocks (BPs) consist of anesthetic injections administered to inactivate the innervation of a specific region of the body, thus blocking signals of pain and sensitivity. BPs are increasingly used in cardiothoracic surgeries, as they can mitigate adverse responses to physiological stress caused by surgery and guarantee a good level of safety. This systematic review aims to evaluate the use of peripheral blocks in pediatric cardiac surgeries (PCS). The platforms PUBMED, SCIELO, LILACS, COCHRANE LIBRARY and EMBASE were used as bases. In total, 192 articles were found, of which 152 were excluded after reading the title and abstract. During the complete reading of the others, 27 were eliminated due to exclusion criteria and thus, only 13 articles were included in this review. Of these, 768 children were evaluated, and 8 types of BPs were assessed in CCPs: Transverse Thoracic Muscular Plane block (BPMTT), erector spinae plane block (BPEE), Paravertebral Nerve block (BNP), Transverse Abdominal Plane block (BPTA), rectus sheath block (BBR), Thoracic Retrolaminar block (BRL), Intercostal Nerve block (BNIC), pleural transverse midpoint process block (BPPMTP). From the studies reviewed, it is inferred that all types of BPs cause an improved recovery in patients undergoing CCPs.